Is There a Role for Probiotics in the Prevention of Preterm Birth? - Yang, Siwen; Reid, Gregor; Challis, John R. G.; Kim, Sung O.; Gloor, Gregory B.; Bocking, Alan D. (Frontiers in Immunology, 2015)
Preterm birth (PTB) continues to be a global health challenge. An over-production of inflammatory cytokines and chemokines, as well as an altered maternal vaginal microbiome has been implicated in the pathogenesis of inflammation/infection-associated PTB. Lactobacillus represents the dominant species in the vagina of most healthy pregnant women. The depletion of Lactobacillus in women with bacterial vaginosis (BV) has been associated with an increased risk of PTB. It remains unknown at what point an aberrant vaginal microbiome composition specifically induces the cascade leading to PTB. The ability of oral or vaginal lactobacilli probiotics to reduce BV occurrence and/or dampen inflammation is being considered as a means to prevent PTB. Certain anti-inflammatory properties of lactobacilli suggest potential mechanisms. To date, clinical studies have not been powered with sufficiently high rates of PTB, but overall, there is merit in examining this promising area of clinical science.